První prípady transmisívního prenosu tularémie na jizní Moravĕ - Cerný, Z; Blazíková, I; Lokajová, M (Casopis lekaru ceskych, 1992)
The authors described two cases of the ulceroglandular form of tularaemia where the infection was transmitted to man after a sting by a tick in the Brno area. The incubation period was two weeks and 11 days resp., the course of the disease, in particular in the female patient was relatively severe and complicated, obviously due to the late establishment of the diagnosis and thus delayed aetiological treatment. The authors recommend to consider a tularaemic aetiology in case of a febrile disease which develops within two weeks after a tick sting, in particular if the site of the prick becomes inflamed and regional lymphadenitis develops.
Keywords: tularemie; Animals; Humans; lidé středního věku; lidé; klíšťata; Female; zvířata; mužské pohlaví; Arachnid Vectors; Male; Czechoslovakia; arachnida jako vektory; Ticks; Middle Aged; Tularemia; ženské pohlaví; Československo